Rehabilitation of damaged coasts using beach nourishment and a case study in Izmit Bay - Mert, Alper. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
Part of Izmit Bay had been filled with excavation waste after the 1999 Earthquake causing beaches around the Bay to lose their natural form and usability. The main purpose of this study is to investigate the existing conditions of a typical fill area and find a feasible solution to reinstate a natural coast. After theoretical and experimental investigations, beach nourishment is proposed as a solution to rehabilitate the coasts of İzmit Bay by transforming them into recreational beaches. The geology, sediment properties, morphological structure and wave regime of the selected pilot site, Derince, is determined by field measurements, laboratory experiments and computer analysis. Along the coastal profile, sediment diameter differs from place to place, and especially in deeper zones, the rate of fine material (silt and clay) increases significantly. Bathymetric measurements indicate that the coastal profile is not in equilibrium. A physical model is established to examine the interaction between the native mixed soil and the granular nourishment sand. Laboratory experiments showed that there is no mixing between the native fine material and nourishment sand. Even after extreme storms, no silt and clay have been found on the nourished nearshore profile. Therefore, it is concluded that the predefined coasts can be rehabilitated using beach nourishment. Using the site specific parameters, alternative beach nourishment designs are developed including calculation of the required sand volumes and the project cost.
Keywords: Coastal ecology -- Turkey -- İzmit.; Estuaries -- Turkey -- İzmit.